Hyperbaric oxygen therapy in stage III C Kienböck disease: Time is bone. Issue 11 (19th November 2022) - Cracchiolo, Andrea N.; Genco, Fabio; Lo Bue, Rosalia; Palmeri, Marco; Tantillo, Diego; Re, Giuseppe; Bonanno, Biagio; Finazzo, Mario; Palma, Daniela Maria
Abstract: Kienböck disease, also known as lunatomalacia, is a rare condition which can lead to progressive wrist pain and abnormal carpal motion. We present the case of a 30‐year‐old patient with Down syndrome who came to our observation for treatment of stage III C Kienböck disease. In September 2019, the patient reported wrist pain with limitation in movements and initially underwent conservative treatment without benefit. In October 2020, pain symptoms and difficult movements with reduced strength worsened and surgical treatment was proposed, but the patient and his family declined. Thereby the patient underwent conservative treatment with hyperbaric oxygen therapy (HBOT) 60 sessions, 100% oxygen at 2.5 absolute atmospheres (ATA), oxygen total time 60 min, once daily, five times per week. After 6 months, a positive clinical and radiological evolution were observed, with an improvement in the patterns of pain, motion, and strength and an almost complete involution of the process of aseptic necrosis of the semilunar. To the best of our knowledge, this is the first report of stage III C Kienböck's disease in Down's syndrome patient treated with HBOT. Abstract : Kienböck disease is a rare condition which can lead to progressive wrist pain and abnormal carpal motion. We present the case of a 30‐year‐old patient with Down syndrome who came to our observation for the treatment of stage III C Kienböck and described the usefulness that HBOT can have in the conservative management of this disease.